Health promotion: The impact of beliefs of health benefits, social relations and enjoyment on exercise continuation. (August 2014) - Nielsen, G.; Wikman, J. M.; Jensen, C. J.; Schmidt, J. F.; Gliemann, L.; Andersen, T. R.
Abstract : The aim of this study was to explore how and why participants in structured exercise intervention programs continue or stop exercising after the program is finished. We conducted four focus group interviews with four groups of middle‐aged and elderly men (total n  = 28) who had participated in exercise interventions involving playing either a team sport (football) or a more individually focused activity (spinning and crossfit). Our results show that different social, organizational and material structures inherent in the different activities shape the subjects' enjoyment of exercise participation, as well as their intention and ability to continue being active. In conclusion, team sport activities seem to be intrinsically motivating to the participants through positive social interaction and play. They are therefore more likely to result in exercise continuation than activities that rely primarily on extrinsic motivation such as the expectation of improved health and well‐being.